Computer Simulation and Animation in Engineering Mechanics: A Critical Review and Analysis - Masri; Suardi; Al-Bahri, Fauzan Putraga (International Journal Education and Computer Studies (IJECS), 2024)
Improving the quality of learning in mechanical engineering is a major challenge in the field of mechanical engineering, especially in understanding complex concepts such as statics and dynamics. This study aims to improve the effectiveness of the use of computer simulation and animation as an innovative learning tool in mechanical engineering. This study used a mixed approach (mixed methods) with a quasi-experimental design involving 94 mechanical engineering students from three universities in Indonesia who were divided into an experimental group using simulation and animation modules (n=50) and a control group using conventional methods (n=50). The results showed that the use of this technology increased students' understanding by 25% compared to 10% in the traditional method, with a significant difference in the post-test (t(92)=3.87, p=0.0002, Cohen's d=0.79). The experimental group also reported a higher level of engagement (85% vs 62%) and a significant reduction in cognitive load (NASA-TLX: 32.4 vs 45.7). Qualitative analysis revealed that visualization helped students connect theory with practical applications, in line with the principles of Cognitive Load Theory and Cognitive-Affective Learning Theory with Media. Although effective, the study identified implementation challenges such as software development costs, educator training needs, and disparities in technology access across institutions in Indonesia. The study concluded that computer simulation and animation have transformative potential to improve the quality of mechanical engineering education, with recommendations for future development through the integration of immersive technologies such as Virtual Reality and Augmented Reality that support the Conceive-Design-Implement-Operate (CDIO) approach in preparing the workforce to face the demands of the Industrial Revolution 4.0.